(NpITANNQ L)QÆTERATUROZNAWSTWA (B:s)E (NNAUK(B. (NZB(B.s (NwIP(B. 73 /s - (N~ERN)QÆW(B. (NNAC(B. (NUN(B-(NT ÆM(B. (N`RÆQ fEDXKOWI^As)E; )Qæ(NN(B-(NT L(B-(NRI ÆM(B. (Nt(B. (Ng(B. (N{EW^ENKA nan uKRAÇNIs)E ((N~ERN)QÆWCÆ (B:s)E [(NB(B. (NW(B.] ;s, 2007)
(NwIPUSK PRISWQ^ENO (B60-(NR)QÆ^^@ NAUKOWOÇ DÆQLXNOSTÆ PROFESORA a(B.(Nr(B. (NwOLKOWA(B. (NwÆN WÆDBIWAÃ PROBLEMATIKU(B, (NKOLO QKOÇ OKRESL@ÃTXSQ NAUKOWO@ DÆQLXNÆST@ W^ENOGO (B((NPREZENTUÃTXSQ RUBRIKAMI (B"(NtEORÆQ LÆTERATURI(B", "(NpOETIKA(B", "(NkOMPARATIWÆSTIKA(B", "æ(NSTORÆQ LÆTERATURI(B", "(NpEREKLADOZNAWSTWO(B", "(NrECENZÆÇ(B). (NpORU[ENÆ W STATTQH PITANNQ ROZGLQDA@TXSQ NA WÆT^IZNQNOMU TA ZARUBÆVNOMU MATERÆALÆ(B. (NoSOBISTÆSTX W^ENOGO ROZKRIWAÃTXSQ U RUBRICÆ (B"(N`WÆLQRÆJ(B", (NNAUKOWIJ DOROBOK WÆDPOWÆDNO PREZENTUÃ (B"(NbÆBLÆOGRAFÆ^NIJ POKAV^IK(B".s)E
(NpRISWQ^(B. 60-(NR)QÆ^^@ NAUK(B. (NDÆQLXNOSTÆ PROF(B. (Na(B. (Nr(B. (NwOLKOWAs)E
Keywords: (Nl)QÆTERATUROZNAWSTWOs)E -- (NzB)QÆRNIKI(B.s)E